ANALISIS PEMERATAAN BEBAN PADA TRANSFORMATOR DARI SISI SEKUNDER TERHADAP PENYALURAN TENAGA LISTRIK DI PT. PLN (PERSERO) UP3 CENGKARENG - Tasdik Darmana; Syarif Hidayat; Miftahul Khoir (Jurnal Ilmiah Teknik, 2023)
The problem in this study is entitled "analysis of load distribution on the transformer from the secondary side to the distribution of electric power at PT. PLN (Persero) UP3 Cengkareng". In accordance with the formulation of the problem in this study, namely finding out how much load is on the distribution transformer BC302 before and after the load equalization analysis is carried out, what is the percentage of load imbalance on the transformer before and after the load distribution analysis is carried out, what are the benefits experienced by PT. PLN (Persero) UP3 Cengkareng after load analysis. The method used in this study is a comparative quantitative method. From the results obtained in this study, with the distribution planning of the BC302 distribution transformer, the power loss due to current in neutral (IN) is 162 A during the day, 6.44 kW before the load is balanced, and 6.289 kW at night 162 A before distribution. kilowatt load, and after the simulated load is balanced, the current flowing to ground is close to 0A. So the more current that flows in the neutral, the greater the power losses.